ANALYSIS OF THE USE OF FICTIONAL TEXT TEACHING MATERIALS IN LITERACY MATERIALS FOR GRADE IV STUDENTS AT THE UPTD OF STATE ELEMENTARY SCHOOL 28 PEUSANGAN - Juliana Safitri; Alfi Syahrin; Hendra Saputra (World Psychology, 2026)
Fiction texts are one type of reading material that plays an important role in literacy learning at the elementary school level. This study aims to analyze the use of fiction text teaching materials in literacy learning for fourth grade students at UPTD SDN 28 Peusangan. This research employed a qualitative approach with a descriptive design. The study was conducted at UPTD SDN 28 Peusangan, Peusangan District, Bireuen Regency, in the 2025/2026 academic year. The research subjects consisted of five fourth-grade teachers and sixteen fourth-grade students. The data sources included primary and secondary data. Primary data were obtained through observations of the learning process and interviews with teachers and students. Secondary data were collected from supporting documents such as teaching modules, ATP, fiction text teaching materials, and learning documentation. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results showed that students’ literacy skills prior to the use of fiction text teaching materials were still relatively low. The implementation of fiction text teaching materials was able to increase student engagement, reading comprehension, vocabulary mastery, and writing skills in a more coherent and structured manner. The conclusion of this study indicates that the use of fiction text teaching materials has a positive impact on improving reading and writing literacy skills of fourth-grade students.